Self-efficacy and burnout in teachers of students with autism spectrum disorder. (April 2017) - Boujut, Emilie; Popa-Roch, Maria; Palomares, Emilie-Anne; Dean, Annika; Cappe, Emilie
Highlights: Perceived stress in teachers of students with ASD is correlated with levels of burnout. Coping strategies of teachers of students with ASD are correlated with levels of burnout. Perceived stress and coping strategies mediate the relationship between perceived self-efficacy and burnout. Emotion-focused coping strategies mediate the relationship between perceived self-efficacy and every dimension of burnout. Abstract: Background: Inclusion in schools of students with autism spectrum disorder (ASD) is a source of stress for teachers and requires a certain amount of adaptation to deal with it. The effects of perceived self-efficacy on burnout in professionals have been substantiated but the indirect effects, mediated by transactional processes of stress and coping, have never been explored in this specific context. This study aims to test the mediating effect of perceived stress and coping strategies on the relationship between perceived self-efficacy and burnout. Method: A sample of 203 teachers of students with ASD filled out four self-report questionnaires measuring perceived self-efficacy, perceived stress, coping strategies, and burnout. A multiple mediation analysis was carried out using the bootstrap procedure. Results: After controlling for the direct effect of perceived self-efficacy on burnout, the indirect effects through transactional processes were significant. The lower the teachers' feeling of self-efficacy, the more they implemented emotion-focused coping strategies, which predict higher burnout in all three of its dimensions. Moreover, the lower the teachers' feeling of self-efficacy, the more they perceived the stressful situation in question as a threat or loss, perceptions that generate more emotional exhaustion. Conclusion: These results enable us to formulate some ideas for improving both the wellbeing of teachers working with students with ASD and the management of such students, and thus their learning abilities and wellbeing in school.